Toner binder

The toner binder with a crystalline polyester resin, formed from a polycondensate of specific components, addresses dispersibility and heat-resistant storage stability issues, enhancing low-temperature fixability and image quality.

JP2024177116APending Publication Date: 2024-12-19SANYO CHEM IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024091791
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-07
Filing Date
2024-06-05
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Toner binders using crystalline polyester resins face challenges with dispersibility and heat-resistant storage stability when toner particles are made smaller for higher image quality, particularly in achieving low-temperature fixability.

Method used

A toner binder comprising a crystalline polyester resin formed from a polycondensate of a polyol component, a polycarboxylic acid component, and a modified silicone compound, with specific molecular compositions and ratios to enhance dispersibility and heat-resistant storage stability.

Benefits of technology

The toner binder achieves excellent dispersibility and heat-resistant storage stability, along with improved low-temperature fixability, as demonstrated by the evaluation results in Tables 1 and 2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177116000001
    Figure 2024177116000001
  • Figure 2024177116000002
    Figure 2024177116000002
Patent Text Reader

Abstract

To provide a toner binder excellent in heat-resistant storage properties, electrification characteristics, and dispersion of crystalline polyester in an amorphous resin.SOLUTION: A toner binder includes a crystalline polyester resin (A) being a polycondensation body of: a polyol component (x); a polycarboxylic acid component (y); and a modified silicone compound (z). The polyol component (x) includes 80 mol% or more of a straight chain aliphatic diol (x1) having an even number of carbon atoms within 2 to 24 carbon atoms, based on a mol number of the polyol component (x). The polycarboxylic acid component (y) includes 80 mol% or more of a straight chain aliphatic dicarboxylic acid (y1) having an odd number of carbon atoms within 3 to 23 carbon atoms, based on a mol number of the polycarboxylic acid component (y). A content (XS) of a silicon element measured by an X-ray fluorescence analysis is 1.0 to 5.0 wt.% based on a weight of the toner binder.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner binder. [Background technology]

[0002] In recent years, along with the promotion of miniaturization, speedup, and high image quality of electrophotographic apparatuses, there has been a strong demand for improving the low-temperature fixability of toners from the viewpoint of energy saving, that is, reducing energy consumption in the fixing process. The toner binder has a significant effect on the toner characteristics as described above. Known examples of the toner binder include polystyrene resin, styrene-acrylic resin, polyester resin, epoxy resin, polyurethane resin, and polyamide resin. Recently, polyester resin has been attracting particular attention because it is easy to balance storage stability and fixability. For example, a toner using a crystalline polyester resin with excellent melting properties and an amorphous resin has been proposed for the purpose of achieving low-temperature fixability (see Patent Document 1). Furthermore, a toner composition containing an amorphous polyester bonded with modified silicone has been proposed for the purpose of improving low-temperature fixing properties and chargeability (see Patent Document 2). However, when the particle size of the toner is reduced to meet the demand for even higher image quality, the dispersibility of the crystalline polyester resin in the toner using the above-mentioned crystalline polyester resin is not sufficient, and improvements in this respect are desired. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-287426 A [Patent Document 2] JP 2023-18981 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a toner binder that is excellent in heat-resistant storage stability, electrostatic chargeability, and dispersibility of a crystalline polyester in an amorphous resin. [Means for solving the problem]

[0005] The present inventors have conducted extensive research and have arrived at the present invention. That is, the present invention provides a toner binder comprising a crystalline polyester resin (A) which is a polycondensate of a polyol component (x), a polycarboxylic acid component (y) and a modified silicone compound (z), wherein the polyol component (x) contains 80 mol % or more of a linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms, based on the number of moles of the polyol component (x), and the polycarboxylic acid component (y) contains 80 mol % or more of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms, based on the number of moles of the polycarboxylic acid component (y), and the silicon element content (X1) measured by fluorescent X-ray analysis is 1.0 to 1.0 mol %. S ) is 1.0 to 5.0% by weight based on the weight of the toner binder. Effect of the Invention

[0006] The toner binder of the present invention is excellent in heat-resistant storage stability, electrostatic chargeability, and dispersibility of the crystalline polyester in the amorphous resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The toner binder of the present invention is a toner binder comprising a crystalline polyester resin (A) which is a polycondensate of a polyol component (x), a polycarboxylic acid component (y) and a modified silicone compound (z), wherein the polyol component (x) contains 80 mol % or more of a linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms, based on the number of moles of the polyol component (x), and the polycarboxylic acid component (y) contains 80 mol % or more of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms, based on the number of moles of the polycarboxylic acid component (y), and the silicon element content (X S) is 1.0 to 5.0% by weight based on the weight of the toner binder.

[0008] <Crystalline polyester resin (A)> The toner binder of the present invention contains a crystalline polyester resin (A) which is a polycondensate of a polyol component (x), a polycarboxylic acid component (y), and a modified silicone compound (z). In addition, in the present invention, "crystalline" means that in differential scanning calorimetry (also referred to as DSC measurement), a DSC curve has a peak top temperature (Tm) of an endothermic peak. The method for measuring the peak top temperature of the endothermic peak of the crystalline polyester resin (A) will be described below. The temperature is measured using a differential scanning calorimeter (e.g., DSC Q20, manufactured by TA Instruments, Inc.). The crystalline polyester resin (A) is heated from 30°C to 180°C at 10°C / min for the first time, then cooled from 180°C to 0°C at 10°C / min, and then heated from 0°C to 180°C for the second time at 10°C / min. The temperature showing the top of the endothermic peak during the second heating process is taken as the endothermic peak top temperature of the crystalline polyester resin (A).

[0009] The crystalline polyester resin (A) in the present invention is a crystalline polyester resin which is a polycondensation product of a polyol component (x), a polycarboxylic acid component (y), and a modified silicone compound (z). The polyol component (x) contains, as an essential component, a linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms, and the polycarboxylic acid component (y) contains, as an essential component, a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms. The modified silicone compound (z) is preferably a modified silicone having at least one functional group selected from a hydroxyl group, an amino group, and a carboxy group. Each of the components (x), (y), and (z) may be used alone or in combination of two or more.

[0010] The polyol component (x) may contain, in addition to the essential component (x1) linear aliphatic diol having an even number of carbon atoms and 2 to 24 carbon atoms, a diol other than (x1) and a trihydric or higher polyol.

[0011] Examples of the straight-chain aliphatic diol (x1) having an even carbon number of 2 to 24 include ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol. From the viewpoint of low-temperature fixability, straight-chain aliphatic diols having an even carbon number of 6 to 12 are preferred, and 1,6-hexanediol, 1,10-decanediol, and 1,12-dodecanediol are more preferred.

[0012] Examples of diols other than (x1) include linear aliphatic diols having an odd number of carbon atoms from 3 to 23, alicyclic diols having 6 to 36 carbon atoms, and / or aromatic diols.

[0013] Examples of the linear aliphatic diol having an odd number of carbon atoms from 3 to 23 include 1,3-propanediol, 1,5-pentanediol, 1,7-heptanediol, 1,9-nonanediol, 1,13-tridecanediol, 1,15-pentadecanediol, and 1,19-nonadecanediol.

[0014] Examples of the alicyclic diol having 6 to 36 carbon atoms include 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,1-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 5-norbornene-2,3-dimethanol, hydrogenated bisphenol A, spiroglycol, isosorbide, and alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) adducts of the above alicyclic diols.

[0015] Examples of the alkylene oxide adduct of the alicyclic diol include an ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as EO) adduct of the alicyclic diol, a propylene oxide (hereinafter, "propylene oxide" may be abbreviated as PO) adduct, and a butylene oxide (hereinafter, "butylene oxide" may be abbreviated as BO) adduct, etc. The average molar number of the alkylene oxide added is preferably 1 to 30, and more preferably 2 to 5.

[0016] Examples of aromatic diols include 1,3-benzenedimethanol, 1,4-benzenedimethanol, bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, and 2,2'-diethylbisphenol F, as well as alkylene oxide adducts of the above aromatic diols.

[0017] Examples of the alkylene oxide adduct of the aromatic diol include an EO adduct, a PO adduct, and a BO adduct of the aromatic diol. The average molar number of the alkylene oxide added is preferably 1 to 15, and more preferably 2 to 5.

[0018] Examples of trihydric or higher polyols include polyhydric aliphatic alcohols (alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, and polyglycerin, sugars and their partial esters, such as sucrose and methyl glucoside, etc.), alkylene oxide adducts of trisphenols (trisphenol PA, etc.) (the number of moles added is preferably 2 to 30), alkylene oxide adducts of novolak resins (including phenol novolak and cresol novolak, etc., the average polymerization degree of which is preferably 3 to 60) (the number of moles added is preferably 2 to 30), and acrylic polyols [copolymers of hydroxyethyl (meth)acrylate and other vinyl monomers, etc.].

[0019] When the polyol component (x) contains a component other than the linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms, from the viewpoint of low-temperature fixability, a linear aliphatic diol having an odd carbon number and 3 to 23 carbon atoms is preferred, and a linear aliphatic diol having an odd carbon number and 5 to 11 carbon atoms is more preferred.

[0020] The polyol component (x) contains 80 mol % or more of a linear aliphatic diol (x1) having an even carbon number of 2 to 24, based on the number of moles of the polyol component (x). Also, (x1) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 100 mol %, based on the number of moles of the polyol component (x). If it is less than 80 mol %, the electrostatic property or heat-resistant storage stability may be deteriorated.

[0021] Examples of the polycarboxylic acid component (y) include the essential component linear aliphatic dicarboxylic acid (y1) having an odd number of carbon atoms and 3 to 23 carbon atoms, as well as aliphatic dicarboxylic acids other than (y1), aromatic dicarboxylic acids having 8 to 20 carbon atoms, trivalent or higher polycarboxylic acids, and anhydrides and lower alkyl (having 1 to 4 carbon atoms) esters of these acids (methyl esters, ethyl esters, isopropyl esters, etc.).

[0022] Examples of the linear aliphatic dicarboxylic acid (y1) having an odd number of carbon atoms and 3 to 23 include malonic acid (3 carbon atoms), glutaric acid (5 carbon atoms), pimelic acid (7 carbon atoms), azelaic acid (9 carbon atoms), and undecanedioic acid (11 carbon atoms). From the viewpoint of low-temperature fixability, linear aliphatic dicarboxylic acids having an odd number of carbon atoms and 5 to 11 carbon atoms are preferred, and glutaric acid, azelaic acid, and undecanedioic acid are more preferred.

[0023] Examples of the aliphatic dicarboxylic acid other than (y1) include linear aliphatic dicarboxylic acids having an even carbon number of 2 to 24. Examples of the linear aliphatic dicarboxylic acid having an even carbon number of 2 to 24 include succinic acid, adipic acid, sebacic acid, dodecanedioic acid, and 1,18-octadecanedicarboxylic acid.

[0024] Examples of the aromatic dicarboxylic acid having 8 to 20 carbon atoms include phthalic acid, terephthalic acid, isophthalic acid, t-butylisophthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid.

[0025] Examples of trivalent or higher polycarboxylic acids include aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid), aliphatic tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid), and vinyl polymers of unsaturated carboxylic acids [number average molecular weight (Mn): 450 to 10,000] (styrene / maleic acid copolymer, styrene / acrylic acid copolymer, styrene / fumaric acid copolymer, etc.), etc. In addition, anhydrides and lower alkyl esters of these acids may also be used.

[0026] When the polycarboxylic acid component (y) contains a component other than the linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms, from the viewpoint of low-temperature fixability, a linear aliphatic dicarboxylic acid having an even carbon number and 2 to 24 carbon atoms is preferred, and a linear aliphatic dicarboxylic acid having an even carbon number and 4 to 12 carbon atoms is more preferred.

[0027] The polycarboxylic acid component (y) contains 80 mol % or more of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number of 3 to 23, based on the number of moles of the polycarboxylic acid component (y). Also, (y1) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 100 mol %, based on the number of moles of the polycarboxylic acid component (y). If it is less than 80 mol %, the electrostatic property or heat-resistant storage stability may be deteriorated.

[0028] From the viewpoint of reacting with at least one of the polyol component (x) and the polycarboxylic acid component (y) to obtain a crystalline polyester resin, the modified silicone compound (z) is preferably a modified silicone having at least one functional group selected from a hydroxyl group, an amino group, and a carboxy group, and more preferably a modified silicone having 1 to 2 of the above functional groups in one molecule.

[0029] Examples of modified silicone compounds having a hydroxyl group include silicone modified with carbinol at both ends (commercially available products include, for example, "X-22-160AS", "KF-6000", "KF-6001", "KF-6002", and "KF-6003" (all manufactured by Shin-Etsu Chemical Co., Ltd.)), silicone modified with carbinol at one end (commercially available products include, for example, "X-22-170BX", "X-22-170DX", "X-22-176DX", and "X-22-176GX-A" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "FM-0411", "FM-0421", and "FM-0425" (all manufactured by JNC Corporation)).

[0030] Examples of modified silicone compounds having an amino group include side-chain amine-modified silicones (commercially available products include, for example, "KF-864", "KF-865", and "KF-868" (all manufactured by Shin-Etsu Chemical Co., Ltd.)), and both-end amine-modified silicones (commercially available products include, for example, "FM-3311", "FM-3321", and "FM-3325" (all manufactured by JNC Corporation)).

[0031] An example of a modified silicone compound having a carboxy group is a side-chain type carboxy modified silicone (a commercially available product is, for example, "X-22-3701E" (manufactured by Shin-Etsu Chemical Co., Ltd.)).

[0032] Of the above modified silicone compounds (z), from the viewpoint of reactivity, modified silicone compounds having a hydroxyl group and modified silicone compounds having an amino group are preferred, and modified silicone compounds having a hydroxyl group are more preferred.

[0033] From the viewpoint of dispersibility, the content of the modified silicone compound (z) is 0.20 to 2.00 mol %, more preferably 0.20 to 1.20 mol %, based on the total number of moles of the monomers constituting the crystalline polyester (A).

[0034] The reaction ratio of the polyol component (x), the polycarboxylic acid component (y) and the modified silicone compound (z) is preferably 1 / 2 to 2 / 1, more preferably 1 / 1.3 to 1.5 / 1, and even more preferably 1 / 1.2 to 1.4 / 1, in terms of the molar ratio of hydroxyl groups to carboxyl groups {[OH] / [COOH]}. When the modified silicone compound (z) is a compound having a hydroxyl group, the above hydroxyl group is the sum of the hydroxyl groups of (x) and the hydroxyl groups derived from (z), and when the modified silicone compound (z) has a carboxyl group, the carboxyl group is the sum of the carboxyl groups of (y) and the carboxyl groups derived from (z).

[0035] In the present invention, the crystalline polyester resin (A) can be produced in the same manner as known polyester production methods, except that the modified silicone compound (z) is used. For example, it can be produced by reacting a component containing a polyol component (x), a polycarboxylic acid component (y), and a modified silicone compound (z) in an inert gas (nitrogen gas, etc.) atmosphere. It is also possible to react the polyol component (x) with the polycarboxylic acid component (y) in advance, and then react the modified silicone compound (z). The reaction temperature is preferably 100 to 280°C, more preferably 120 to 250°C, and further preferably 140 to 235°C, from the viewpoint of ensuring the polycondensation reaction. From the viewpoint of ensuring that the polycondensation reaction is carried out, the reaction time is preferably 30 minutes or more, and more preferably 2 to 40 hours.

[0036] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxybis(triethanolaminate), titanium dihydroxybis(triethanolaminate), titanium monohydroxytris(triethanolaminate), titanyl bis(triethanolaminate) and intramolecular polycondensates thereof, etc.}, and catalysts described in JP-A-2007-11307 (titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, titanium diisopropoxyditerephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.), and zinc acetate. Of the esterification catalysts, titanium-containing catalysts are preferred from the viewpoint of low-temperature fixability, and the catalysts described in JP-A-2006-243715 and JP-A-2007-11307 are more preferred.

[0037] In the present invention, the crystalline polyester resin (A) is heated using a differential scanning calorimeter in a first step from 30° C. to 180° C. at 10° C. / min, then cooled from 180° C. to 0° C. at 10° C. / min, and then heated in a second step from 0° C. to 180° C. at 10° C. / min. The peak top temperature (Tm) of the endothermic peak during the second heating step is preferably 40 to 125° C., more preferably 60 to 85° C. If it is 40° C. or higher, the heat-resistant storage stability is good, and if it is 125° C. or lower, the low-temperature fixability is good.

[0038] In the present invention, the crystalline polyester resin (A) preferably has an endothermic amount of 40 to 130 J / g, more preferably 80 to 120 J / g, at the endothermic peak having the above peak top temperature (Tm), from the viewpoint of low-temperature fixability.

[0039] In the present invention, the acid value of the crystalline polyester resin (A) is preferably from 0 to 20 mgKOH / g, more preferably from 0.1 to 5 mgKOH / g, from the viewpoints of electrostatic chargeability and heat-resistant storage stability.

[0040] In the present invention, the hydroxyl value of the crystalline polyester resin (A) is preferably from 0 to 50 mgKOH / g, more preferably from 1 to 30 mgKOH / g, from the viewpoints of electrostatic chargeability and heat-resistant storage stability.

[0041] In the present invention, the number average molecular weight (Mn) of the crystalline polyester resin (A) as measured by gel permeation chromatography (GPC) is preferably from 2,000 to 50,000, and more preferably from 2,000 to 25,000, from the viewpoints of low-temperature fixability and image strength.

[0042] In the present invention, the weight average molecular weight (Mw) of the crystalline polyester resin (A) as measured by gel permeation chromatography (GPC) is preferably from 10,000 to 100,000, and more preferably from 10,000 to 50,000, from the viewpoints of low-temperature fixability and image strength.

[0043] <Cyclic ester compounds> The toner binder of the present invention preferably contains a cyclic ester compound which is a reaction product of a polyol component (x) and a polycarboxylic acid component (y) in addition to the essential component crystalline polyester resin (A) from the viewpoint of low temperature fixability.

[0044] Examples of the cyclic ester compound include compounds in which the above-mentioned polyol component (x) and the polycarboxylic acid component (y) are condensed in equimolar amounts to form a cyclic ester. Specifically, cyclic ester compounds of linear aliphatic diols having 2 to 24 carbon atoms and linear aliphatic dicarboxylic acids having 2 to 24 carbon atoms (cyclic condensation products of sebacic acid and 1,6-hexanediol (1:1 molar ratio), cyclic condensation products of sebacic acid and 1,6-hexanediol (2:2 molar ratio), cyclic condensation products of sebacic acid and 1,6-hexanediol (3:3 molar ratio), cyclic condensation products of sebacic acid and 1,6-hexanediol (4:4 molar ratio), cyclic condensation products of sebacic acid and 1,6-hexanediol (5:5 molar ratio), cyclic condensation products of 1,9-nonanediol and dodecanedioic acid (2:2 molar ratio), cyclic condensation products of 1,5-pentanediol and sebacic acid (2:2 molar ratio) cyclic condensation products of ethylene glycol and terephthalic acid (1:1 molar ratio), cyclic condensation products of ethylene glycol and isophthalic acid (2:2 molar ratio), cyclic condensation products of ethylene glycol and terephthalic acid (3:3 molar ratio), cyclic condensation products of ethylene glycol and terephthalic acid (5:5 molar ratio), cyclic condensation products of ethylene glycol and terephthalic acid (10:10 molar ratio), etc.) of linear aliphatic diols having 2 to 24 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms.

[0045] In the present invention, the cyclic ester compound can be produced in the same manner as in the known polyester production method, but the yield can be increased by producing it via depolymerization of an aliphatic polyester or an aliphatic ester oligomer. For example, it can be produced by reacting a polyol component (x) with a polycarboxylic acid component (y) in an inert gas (nitrogen gas, etc.) atmosphere. It can also be obtained as a by-product during the production of the crystalline polyester resin (A), and the amount of the cyclic ester compound produced can be adjusted by the charging ratio of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms. For example, the amount of the cyclic ester compound produced can be reduced by increasing the charging ratio of a linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms in the polyol component (x) and increasing the charging ratio of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms in the polycarboxylic acid component (y).

[0046] <Toner binder> The toner binder of the present invention may contain the crystalline polyester resin (A) which is an essential component, but preferably contains a cyclic polyester compound.

[0047] The content of the crystalline polyester resin (A), which is a polycondensate of the polyol component (x), the polycarboxylic acid component (y) and the modified silicone compound (z) in the toner binder is preferably 93.0 to 99.3% by weight, more preferably 94.0 to 99.3% by weight, based on the weight of the toner binder.

[0048] The content of the cyclic ester compound, which is a reaction product of the polyol component (x) and the polycarboxylic acid component (y) in the toner binder, is preferably 0.7 to 7.0% by weight, and more preferably 0.7 to 6.0% by weight, based on the weight of the toner binder, from the viewpoints of chargeability and heat-resistant storage stability.

[0049] The content of silicon element in the toner binder measured by X-ray fluorescence analysis (X S) is 1.0 to 5.0% by weight, preferably 1.5 to 4.0% by weight, based on the weight of the toner binder. If it is less than 1.0% by weight, the dispersibility is poor, and if it exceeds 5.0% by weight, the dispersibility is poor. S Specifically, the toner binder containing the crystalline polyester resin (A) can be measured by fluorescent X-ray analysis according to the method described in JIS K 0119-1969.

[0050] The toner binder of the present invention may be produced in any manner as long as it contains the crystalline polyester resin (A) and, if necessary, a cyclic ester compound, and the crystalline polyester resin (A) may be used as the toner binder as is. For example, the toner binder may be produced by reacting a component containing a polyol component (x), a polycarboxylic acid component (y) and a modified silicone compound (z) in an inert gas (nitrogen gas, etc.) atmosphere. In addition, the toner binder may be produced by first reacting the polyol component (x) with the polycarboxylic acid component (y) to produce a cyclic ester compound, then producing the crystalline polyester resin (A), and mixing the crystalline polyester resin (A) with the cyclic ester compound, etc.

[0051] The toner binder of the present invention may be used as a toner by mixing with various additives such as other known binder resins for toners, colorants, releasing agents, charge control agents, and fluidizing agents.

[0052] As the other binder resin for toner, a non-crystalline resin is preferable, and examples thereof include a non-crystalline polyester resin, a non-crystalline vinyl resin, a non-crystalline epoxy resin, a non-crystalline polycarbonate resin, and a non-crystalline polyurethane resin. Among the above binder resins, the amorphous polyester resin (B) is preferred from the viewpoint of low-temperature fixability.

[0053] The composition of the amorphous polyester resin (B) is not particularly limited as long as it is an amorphous polyester resin that is a polycondensation product of an alcohol component (X) and a carboxylic acid component (Y). In the present invention, the term "amorphous" means that when the transition temperature of a sample is measured using a differential scanning calorimeter, there is no peak top temperature of the endothermic peak.

[0054] Examples of the alcohol component (X) of the amorphous polyester resin (B) include alkylene glycols having 2 to 12 carbon atoms, polyhydric aliphatic alcohols having a valence of three or more, alkylene oxide adducts of bisphenol A (the number of moles added is preferably 2 to 30), and alkylene oxide adducts of novolak resins (the number of moles added is preferably 2 to 30). Examples of the carboxylic acid component (Y) include aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, etc.) and aromatic polycarboxylic acids having 9 to 20 carbon atoms (trimellitic acid, pyromellitic acid, etc.). As the carboxylic acid component (Y), anhydrides and lower alkyl (having 1 to 4 carbon atoms) esters (methyl ester, ethyl ester, isopropyl ester, etc.) of these carboxylic acids may be used, or the anhydrides or lower alkyl esters may be used in combination with the above-mentioned carboxylic acids.

[0055] Of the alcohol components (X) used in the amorphous polyester resin (B), from the viewpoints of low-temperature fixing ability and image strength, preferred are EO adducts of bisphenol A (average number of moles added: 2 to 3) and PO adducts of bisphenol A (average number of moles added: 2 to 3). Of the carboxylic acid components (Y), preferred are terephthalic acid, adipic acid and trimellitic anhydride from the viewpoints of low-temperature fixing ability and image strength.

[0056] The amorphous polyester resin (B) may be, for example, a linear polyester resin (B1) or a non-linear polyester (branched or crosslinked polyester) resin (B2), each of which may be used alone or in combination of two or more. The linear polyester resin (B1) and the non-linear polyester resin (B2) may also be mixed and used. From the viewpoint of achieving both low-temperature fixability and hot offset resistance, the amorphous polyester resin is preferably composed of a linear polyester resin (B1) and a non-linear polyester resin (B2). From the viewpoint of achieving both low-temperature fixability and hot offset resistance, the weight ratio of the linear polyester resin (B1) to the non-linear polyester resin (B2) ((B1) / (B2)) is preferably 10 / 90 to 90 / 10, more preferably 15 / 85 to 85 / 15, even more preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30.

[0057] The glass transition temperature (Tg) of the amorphous polyester resin (B) is preferably from 40 to 75°C, more preferably from 45 to 72°C, and further preferably from 50 to 70°C.

[0058] The acid value of the amorphous polyester resin (B) is preferably 30 mgKOH / g or less, and more preferably 1 to 25 mgKOH / g.

[0059] The hydroxyl value of the amorphous polyester resin (B) is preferably 60 mgKOH / g or less, and more preferably 1 to 60 mgKOH / g.

[0060] The Mw of the amorphous polyester resin (B) is preferably 4,000 to 150,000, and more preferably 5,000 to 90,000.

[0061] The 1 / 2 drop temperature of the amorphous polyester resin (B) is preferably from 80 to 170°C, and more preferably from 95 to 150°C. Two or more types of amorphous polyester resin (B) having different 1 / 2 drop temperatures may be used in combination. A combination of a resin having a 1 / 2 drop temperature of 80°C or more and less than 115°C and a resin having a 1 / 2 drop temperature of 115°C or more and 170°C or less is preferred, and a combination of a resin having a 1 / 2 drop temperature of 85°C or more and less than 115°C and a resin having a 1 / 2 drop temperature of 120°C or more and 160°C or less is more preferred.

[0062] The content of the amorphous polyester resin (B) is preferably 1 to 99 parts by weight, more preferably 5 to 95 parts by weight, and even more preferably 10 to 90 parts by weight, based on 100 parts by weight in total of the toner binder of the present invention and other binder resins for toner. When the amorphous polyester resin (B) is contained, the content of the toner binder of the present invention is preferably 1 to 99 parts by weight, more preferably 5 to 95 parts by weight, and even more preferably 10 to 90 parts by weight, based on 100 parts by weight of the total of the toner binder of the present invention and other binder resins for toner.

[0063] The colorant preferably contains at least one selected from the group consisting of black colorants, blue colorants, red colorants and yellow colorants. As the colorant, any dye, pigment, etc. used as a toner colorant can be used. Specific examples of the pigment include carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Solvent Yellow (21, 77, 114, etc.), Pigment Yellow (12, 14, 17, 83, etc.), India Fast Orange, Irgasin Red, Paranitoaniline Red, Toluidine Red, Solvent Red (17, 49, 128, 5, 13, 22, 48·2, etc.), Disperse Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Solvent Blue (25, 94, 60, 15·3, etc.), Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orasol Brown B, and Oil Pink OP. If necessary, magnetic powder (powders of ferromagnetic metals such as iron, cobalt and nickel, and compounds such as magnetite, hematite and ferrite) may be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 2 to 15 parts by weight, based on 100 parts by weight of the toner binder of the present invention and other toner binder resins in total. When magnetic powder is used, the content of the magnetic powder is preferably 20 to 150 parts by weight, more preferably 30 to 120 parts by weight, based on 100 parts by weight of the toner binder of the present invention and other toner binder resins in total.

[0064] Examples of the release agent include natural waxes (beeswax, carnauba wax, montan wax, etc.), petroleum waxes (paraffin wax, microcrystalline wax, petrolatum, etc.), synthetic waxes (Fischer-Tropsch wax, polyethylene wax, polypropylene wax, oxidized polyethylene wax, oxidized polypropylene wax, etc.), and synthetic ester waxes (fatty acid esters synthesized from fatty acids having 10 to 30 carbon atoms and alcohols having 10 to 30 carbon atoms, etc.), and it is preferable to contain one or more types selected from the group consisting of these release agents. The content of the release agent is preferably 30 parts by weight or less, more preferably 0.5 to 20 parts by weight, and even more preferably 1 to 10 parts by weight, based on 100 parts by weight of the total of the toner binder of the present invention and other binder resins for toners.

[0065] The melting point of the release agent is preferably from 40 to 90°C, more preferably from 45 to 85°C, and particularly preferably from 50 to 80°C, from the viewpoint of low-temperature fixability.

[0066] The kinetic viscosity of the release agent at 100° C. is preferably 3 to 20 mm from the viewpoint of low-temperature fixability. 2 / s, and more preferably 4 to 19 mm 2 / s, particularly preferably 5 to 18 mm 2 / s. The kinetic viscosity at 100° C. can be measured by the method of JIS K2283.

[0067] The charge control agent may contain either a positively charged charge control agent or a negatively charged charge control agent, and examples thereof include nigrosine dyes, triphenylmethane dyes containing tertiary amines as side chains, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing quaternary ammonium bases, metal-containing azo dyes, copper phthalocyanine dyes, salicylic acid metal salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, halogen-substituted aromatic ring-containing polymers, etc. The content of the charge control agent may be 0 to 20 parts by weight, preferably 0.1 to 10 parts by weight, more preferably 0.5 to 7.5 parts by weight, based on 100 parts by weight of the total of the toner binder and the binder resin of the present invention.

[0068] Examples of the fluidizing agent include silica, titania, alumina, fatty acid metal salt, silicone resin particles, and fluororesin particles, and two or more of them may be used in combination. From the viewpoint of the chargeability of the toner, silica is preferable. From the viewpoint of the transferability of the toner, the silica is preferably hydrophobic silica. The content of the fluidizing agent may be 0 to 10 parts by weight, preferably 0 to 5 parts by weight, and more preferably 0.1 to 4 parts by weight, based on 100 parts by weight of the total of the toner binder of the present invention and other binder resins for toner.

[0069] The total weight of additives such as colorants, release agents, charge control agents, and fluidizing agents may be 3 to 70% by weight, preferably 4 to 58% by weight, and more preferably 5 to 50% by weight, based on the toner weight. By keeping the composition ratio of the toner within the above range, it is possible to easily obtain a toner with good charging characteristics.

[0070] The volume average particle diameter (D50) of the toner is preferably from 1 to 15 μm, more preferably from 2 to 10 μm, and particularly preferably from 3 to 7 μm.

[0071] The method for producing the toner is not particularly limited, and the toner may be obtained by a known kneading and grinding method, a suspension polymerization method described in JP-B-10231 / 1961, JP-A-53856 / 1984, and JP-A-61842 / 1984, an emulsion polymerization method represented by a soap-free polymerization method in which a toner is produced by directly polymerizing a monomer in the presence of a water-soluble polymerization initiator that is soluble in the monomer, an interfacial polymerization method such as a microcapsule production method, an in situ polymerization method, a coacervation method, an association polymerization method in which at least one type of fine particles are aggregated to obtain a toner of a desired particle size as disclosed in JP-A-106473 / 1987 and JP-A-186253 / 1988, a dispersion polymerization method characterized by monodispersion, a dissolution suspension method in which a necessary resin is dissolved in a non-water-soluble organic solvent and then converted into a toner in water, or a method in which the toner is dispersed in carbon dioxide in a supercritical state.

[0072] For example, when a toner is obtained by a kneading and pulverizing method, the components constituting the toner except for the fluidizing agent are dry-blended using a Henschel mixer, a Nauta mixer, a Banbury mixer, or the like, and then melt-kneaded using a continuous mixer such as a twin-screw kneader, an extruder, a continuous kneader, or a three-roll mill, and then coarsely pulverized using a mill or the like, and finally atomized using an air flow type pulverizer or the like, and further the particle size distribution is adjusted using a classifier such as an elbow jet to produce fine particles having a volume average particle size (D50) of 4 to 12 μm, and then the fluidizing agent is mixed in a mill or the like to produce the toner.

[0073] For example, when a toner is obtained by a solution suspension method, the components constituting the toner except for the fluidizing agent are dissolved or dispersed in an organic solvent to form an oil phase, and then the oil phase is mixed with an aqueous phase containing a surfactant to form fine particles. Further, the organic solvent is removed from the mixture of the oil phase and the aqueous phase, and the toner particles are separated and classified, and finally, the fluidizing agent is mixed to produce the toner.

[0074] The toner using the toner binder of the present invention is fixed to a support (paper, polyester film, etc.) by a copier, printer, etc. to form a recording material. As a method for fixing to a support, a known hot roll fixing method, flash fixing method, etc. can be used.

[0075] The toner using the toner binder of the present invention can be preferably used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More preferably, it can be used for developing full-color electrostatic images or magnetic latent images. EXAMPLES

[0076] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following, "parts" refers to parts by weight unless otherwise specified.

[0077] The physical properties of the crystalline polyester resin, the amorphous polyester resin, the toner, etc. were measured by the following methods.

[0078] <Method for measuring the peak top temperature of the endothermic peak of the crystalline polyester resin (A)> The measurement was performed using a differential scanning calorimeter {"DSCQ20" [manufactured by TA Instruments, Inc.]}. The crystalline polyester resin (A) was heated for the first time from 30°C to 180°C at 10°C / min, then cooled from 180°C to 0°C at 10°C / min, and then heated for the second time from 0°C to 180°C at 10°C / min. The temperature showing the top of the endothermic peak during the second heating process was determined as the peak top temperature of the endothermic peak of the crystalline polyester resin (A).

[0079] <Amount of heat absorbed at the endothermic peak of crystalline polyester resin (A)> In the DSC curve during the second heating process observed under the same measurement conditions as in the measurement of the peak top temperature of the endothermic peak, a straight line was drawn connecting the point closest to the peak on the baseline below the endothermic peak endothermic onset temperature (T0) and the point closest to the peak on the baseline above the endothermic peak end point temperature, thereby calculating the amount of endotherm in the endothermic peak having the peak top temperature of the endothermic peak.

[0080] <Weight average molecular weight (Mw)> The weight average molecular weight (Mw) was measured under the following conditions using a sample solution obtained by dissolving the polyester resin in tetrahydrofuran (THF) and filtering off the insoluble matter with a glass filter. Equipment: Tosoh Corporation HLC-8120 Column: TSK GEL GMH6 x 2 (Tosoh Corporation) Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF Solution injection volume: 100μl Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) manufactured by Tosoh Corporation (molecular weight: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000)

[0081] <Acid value and hydroxyl value> The measurement was performed according to the method specified in JIS K0070, except that the measurement solvent for the acid value was a mixed solvent of acetone, methanol, and toluene (weight ratio of acetone:methanol:toluene=12.5:12.5:75), and the measurement solvent for the hydroxyl value was toluene.

[0082] <1 / 2 temperature drop> Using a constant test force extrusion-type capillary rheometer flow tester {Shimadzu Corporation, CFT-500D}, 1 g of the measurement sample was heated at a heating rate of 6°C / min while applying a load of 1.96 MPa with the plunger and extruding it from a nozzle of 1 mm diameter and 1 mm length. A graph was drawn of "plunger drop amount (flow value)" vs. "temperature," and the temperature corresponding to 1 / 2 of the maximum plunger drop amount was read from the graph. This value (the temperature when half of the measurement sample had flowed out) was determined as the 1 / 2 drop temperature.

[0083] <Method of measuring glass transition temperature (Tg)> The measurement was performed using a differential scanning calorimeter (DSC Q20, manufactured by TA Instruments) according to the method (DSC method) specified in ASTM D3418-82 under the following conditions. (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35℃ for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetric curve measured in the process of (5) was analyzed to determine the glass transition temperature.

[0084] <Toner volume average particle size (D50) (μm), number average particle size (μm), particle size distribution (volume average particle size / number average particle size)> Measurements were performed using a Coulter counter [product name: Multisizer III (manufactured by Beckman Coulter, Inc.)]. First, 0.1 to 5 mL of a surfactant (alkylbenzene sulfonate) was added as a dispersant to 100 to 150 mL of an electrolyte solution, ISOTON-II (manufactured by Beckman Coulter). 2 to 20 mg of a measurement sample was then added, and the electrolyte solution in which the sample was suspended was dispersed for approximately 1 to 3 minutes using an ultrasonic disperser. The toner volume and number were measured using a 50 μm aperture with the above-mentioned measuring device, and the volume distribution and number distribution were calculated. From the distribution obtained, the volume average particle diameter (D50) (μm), number average particle diameter (μm), and particle size distribution (volume average particle diameter / number average particle diameter) of the toner were obtained.

[0085] Silicon content measured by X-ray fluorescence analysis (X S )> The toner binder of the present invention was measured using fluorescent X-ray analysis as follows, and the silicon content (Xs) (wt%) in the toner binder was calculated. The obtained value was multiplied by the weight proportion of the crystalline polyester resin (A) in the toner binder to calculate the silicon content (Xs) (wt%). The measurement of fluorescent X-rays for each element conforms to JIS K 0119-1969, and specifically, is as follows. As the measuring device, a wavelength-dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical) and dedicated software "SuperQ ver.5.3A" (manufactured by PANalytical) attached for setting measurement conditions and analyzing measurement data are used. Note that Rh is used as the anode of the X-ray tube, the measurement atmosphere is helium, and the measurement diameter (collimator mask diameter) is 30 mm. In addition, when measuring light elements, a gas flow detector is used, and when measuring heavy elements, a xenon shield detector or a scintillation detector is used for detection. As the measurement sample, a Mylar film (manufactured by Spectris Co., Ltd.) is attached to a measurement cup (manufactured by Spectris Co., Ltd.) with a diameter of 37.5 mm, and 5 g of the sample is placed on the Mylar film and flattened. Measurement is performed under the above conditions, elements are identified based on the peak positions of the obtained X-rays, and the concentration is calculated from the counting rate (unit: cps), which is the number of X-ray photons per unit time. The content (Xs) (weight %) of silicon element was calculated by quantitative analysis by calculation using qualitative and quantitative analysis software "OMNIAN". For example, the channel of element Si is observed at a diffraction angle (2θ) = 109.2° when PE is used as the spectroscopic crystal. The counting rate (unit: cps) of X-rays is measured. At this time, the accelerating voltage and current value of the X-ray generator are 24 kV and 100 mA, respectively.

[0086] <Method for Measuring Content of Cyclic Ester Compound> The content of the cyclic ester compound in the toner binder can be measured by liquid chromatography (hereinafter abbreviated as LC), and the measurement was performed under the following conditions. The device used was manufactured by Shimadzu Corporation. LC: LC-30 Nexera Ion source: ESI MS: LCMS-8030 <LC Measurement Conditions> Mobile phase: A; 10 mM ammonium acetate aqueous solution / methanol = 80 / 20 B; Methanol LC Time Program: A / B = 25 / 75 → 5 / 95 (v / v%) Ratio of Solution B: 75% (0 min), Ratio of Solution B: 95% (10 min), Ratio of Solution B: 95% (31 min), Ratio of Solution B: 100% (32 min), Ratio of Solution B: 100% (35 min), Ratio of Solution B: 75% (36 min), STOP (40 min) Flow rate: 0.3 mL / min Auto sampler: Injection volume 1 μL, Sample cooler 25°C Column: InertSustainSwift (manufactured by GL Sciences Inc., particle size 1.9 μm, inner diameter 2.1 mm, length 50 mm) Column oven: 40°C Ionization mode: ESI(+) Analysis mode: SCAN m / z100~1500 Interface temperature: 350°C DL temperature: 250°C Nebulizer gas flow rate: 3 L / min Heat block temperature: 400°C Drying gas flow rate: 15 L / min <Sample Solution Preparation Method> 1) Put 0.96 g of toner or toner binder into a screw bottle and dissolve it with 8.64 g of tetrahydrofuran (hereinafter referred to as THF). 2) After dissolution, add 28 g of methanol for LC / MS to the screw bottle to precipitate the undissolved matter. 3) Use a centrifuge to sediment the undissolved matter at 2000 rpm for 5 minutes. 4) Filter the supernatant obtained in 3) using a syringe and a membrane filter, and transfer it to a dedicated vial to obtain a sample solution. 5) Measure a part of the sample solution by LC / MS. <Calculation Method for Content of Cyclic Ester Compound> 6) Calculate the THF-methanol soluble content from the solid content of the sample solution in 5) and the resin sample amount. Solid content measurement conditions: After drying in a circulating air oven at 150°C for 45 minutes, cool in a desiccator. 7) Calculate the ratio of the cyclic ester compound from the area ratio of LC / MS. 8) The amount of the cyclic ester compound in the toner or toner binder is determined by multiplying the THF methanol soluble matter by the area ratio of the cyclic ester compound. The content of the cyclic ester compound is calculated as follows, for example, when the alcohol component (x) is 1,6-hexanediol and the carboxylic acid component (y) is sebacic acid. In LC-MS measurement, when ionized with ammonium ions, the molecular weight (m / z) of a cyclic condensate of sebacic acid and 1,6-hexanediol (1:1 molar ratio) is 302, the molecular weight (m / z) of a cyclic condensate of sebacic acid and 1,6-hexanediol (2:2 molar ratio) is 587, and the molecular weight (m / z) of a cyclic condensate of sebacic acid and 1,6-hexanediol (3:3 molar ratio) is 871. The total peak area of ​​the molecular weights derived from the above cyclic substances detected by LC-MS is divided by the total area of ​​the toner or toner binder. In addition, when two or more types of alcohol components (x) or carboxylic acid components (y) are used in combination, the peak area values ​​of the molecular weights of the cyclic ester compounds of possible combinations are summed up and similarly divided by the area of ​​the entire toner or toner binder.

[0087] Example 1 [Synthesis of toner binder (D-1) containing crystalline polyester resin (A-1)] In a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer and a nitrogen inlet tube, 481 parts (51.29 mol%) of 1,12-dodecanediol, 419 parts (48.04 mol%) of azelaic acid, 100 parts (0.67 mol%) of "KF-6002", and 1.5 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were placed and reacted for 8 hours under a nitrogen stream at 160°C while distilling off the generated water. Next, the temperature was gradually raised to 210°C, and the reaction was carried out for 4 hours under a nitrogen stream while distilling off the generated water, and the reaction was further carried out under a reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value reached 1 mgKOH / g. The resin taken out was cooled to room temperature, pulverized and granulated to obtain a toner binder (D-1) containing a crystalline polyester resin (A-1). The peak top temperature (Tm) of the endothermic peak of the crystalline polyester resin (A-1) was 74°C, the endothermic amount at the endothermic peak was 101 J / g, the weight average molecular weight (Mw) was 22,000, the acid value was 1 mg KOH / g, the hydroxyl value was 17 mg KOH / g, the silicon content was 3.8 wt%, and the cyclic ester compound content was 1.0 wt%.

[0088] <Examples 2 to 10> [Synthesis of toner binders (D-2) to (D-10) containing crystalline polyester resins (A-2) to (A-10)] Toner binders (D-2) to (D-10) containing crystalline polyester resins (A-2) to (A-10) were obtained in the same manner as in Example 1, except that the raw materials listed in Examples 2 to 7 in Table 1 were used. The peak top temperature (Tm) of the endothermic peak, the endothermic amount at the endothermic peak, the weight average molecular weight (Mw), the acid value, the hydroxyl value, the silicon element content, and the cyclic ester compound content of the obtained crystalline polyester resins are shown in Table 1.

[0089] <Comparative Examples 1 to 6> [Synthesis of Toner Binders (DR-1) to (DR-6) Containing Crystalline Polyester Resins (AR-1) to (AR-6)] Toner binders (DR-1) to (DR-6) containing crystalline polyester resins (AR-1) to (AR-6) were obtained in the same manner as in Example 1, except that the raw materials shown in Comparative Examples 1 to 6 in Table 2 were used. The peak top temperature (Tm) of the endothermic peak, the endothermic amount at the endothermic peak, the weight average molecular weight (Mw), the acid value, the hydroxyl value, the silicon element content, and the cyclic ester compound content of the obtained crystalline polyester resins are shown in Table 2.

[0090] [Table 1]

[0091] [Table 2]

[0092] The toner binders containing the crystalline polyester resins obtained in Examples 1 to 10 and Comparative Examples 1 to 6 were evaluated by the following methods. The results are shown in Tables 1 and 2. [Evaluation method] The following describes the measurement methods, evaluation methods, and judgment criteria for the dispersibility in amorphous polyester resin of the crystalline polyester resin obtained in Examples 1 to 10 and Comparative Examples 1 to 6 (maximum particle size and average particle size of the crystalline polyester resin in the amorphous polyester resin), as well as the low-temperature fixability, electrostatic property, heat-resistant storage stability, and fixing strength of the toner using the toner binder containing the crystalline polyester resin obtained in Examples 1 to 10 and Comparative Examples 1 to 6 and the amorphous polyester resin.

[0093] <Dispersibility of Crystalline Polyester Resins Obtained in Examples 1 to 10 and Comparative Examples 1 to 6 in Amorphous Polyester Resins> (Maximum and average particle size of crystalline polyester resin in amorphous polyester resin) The toner binder (D) containing the crystalline polyester resin (A) obtained in Examples 1 to 10 and Comparative Examples 1 to 6 was melt-kneaded with the following amorphous polyester resin (B-1) and amorphous polyester resin (B-2) to prepare evaluation samples, and the dispersion state of the crystalline polyester resin (A) in the evaluation samples was evaluated.

[0094] [Synthesis of amorphous polyester resin (B-1)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 730 parts (60 mol%) of bisphenol A·EO 2-mol adduct (manufactured by Sanyo Chemical Industries, Ltd., "Hymer BPE-20"), 194 parts (30 mol%) of terephthalic acid, 76 parts (10 mol%) of trimellitic anhydride, and 2.5 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were placed and reacted at 220°C for 20 hours while distilling off the water produced. The reaction was further carried out under reduced pressure of 0.5 to 2.5 kPa, and when the half-drop temperature reached 131°C, the resin was taken out using a steel belt cooler. The resin taken out was pulverized into particles to obtain amorphous polyester resin (B-1). The amorphous polyester resin (B-1) had a 1 / 2 drop temperature of 131° C., a glass transition temperature Tg of 60° C., an acid value of 1 mgKOH / g, a hydroxyl value of 59 mgKOH / g, and a weight average molecular weight Mw of 90,000.

[0095] [Synthesis of amorphous polyester resin (B-2)] In another reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 722 parts (58 mol%) of bisphenol A·EO 2-mol adduct (manufactured by Sanyo Chemical Industries, Ltd., "Hymer BPE-20"), 269 parts (41 mol%) of terephthalic acid, and 3.0 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were placed, and the temperature was raised to 230°C under a reduced pressure of 0.5 to 2.5 kPa while distilling off the water produced, and the reaction was continued until the acid value was less than 2 mgKOH / g. Then, the reaction was cooled to 180°C, and 9 parts (1 mol%) of trimellitic anhydride were added, and the reaction was continued for 1 hour under normal pressure, and the resin was taken out. After cooling to room temperature, the resin was crushed and granulated to obtain amorphous polyester resin (B-2). The amorphous polyester resin (B-2) had a 1 / 2 drop temperature of 99°C, a glass transition temperature (Tg) of 57°C, an acid value of 5 mgKOH / g, a hydroxyl value of 36 mgKOH / g, and a weight average molecular weight (Mw) of 8,000.

[0096] [Creating evaluation samples and measuring dispersion state] 10 parts of toner binder (D) containing crystalline polyester resin (A), 27 parts of amorphous polyester resin (B-1) and 63 parts of amorphous polyester resin (B-2) were premixed using a Henschel mixer [FM10B, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], and then kneaded with a twin-screw kneader [PCM-30, manufactured by Ikegai Corporation]. Using the resulting mixture, a cross section of the mixture observed with a transmission electron microscope (TEM) was created as follows. The resulting mixture was embedded in a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.), cut to a thickness of 60 nm with an ultrasonic ultramicrotome (EM5, manufactured by Leica), and ruthenium stained with a vacuum staining device (manufactured by Filgen Co., Ltd.). Thereafter, the dispersion state of the crystalline polyester resin was observed from the cross section of the resulting mixture using a transmission electron microscope (H7500, manufactured by Hitachi High-Technologies Corporation) at an accelerating voltage of 120 kV. The longest diameter of the crystalline polyester resin in the entire observed image was taken as the maximum particle size. In addition, randomly selected enlarged images (x1000) were processed using the free software "Image J" according to the following procedure, and the calculated "mean feret" was taken as the average particle size of the crystalline polyester resin. 1. image type → 8bit 2.line → analyze → set scale → known distance 5.0 3.process → binary → median filter 10 4.image → adjust → threshold 5.process → binary → fill holl 6.Analyze particles (set mesearements → feret diameter)

[0097] <Low temperature fixability, chargeability, heat resistant storage stability and fixation strength of toners using toner binders containing crystalline polyester resins and amorphous polyester resins obtained in Examples 1 to 10 and Comparative Examples 1 to 6> Toners were prepared by the following method using the toner binders containing the crystalline polyester resins (A) obtained in Examples 1 to 10 and Comparative Examples 1 to 6, and the amorphous polyester resins (B-1) and (B-2), and the low-temperature fixing property, chargeability, heat-resistant storage stability, and fixing strength were evaluated. [Toner manufacturing] To 10 parts of toner binder (D) containing crystalline polyester resin (A), 27 parts of amorphous polyester resin (B-1), and 63 parts of amorphous polyester resin (B-2), 8 parts of pigment carbon black "MA-100" [manufactured by Mitsubishi Chemical Corporation] as a colorant, 4 parts of paraffin wax "HNP-9" [manufactured by Nippon Seiro Co., Ltd.] as a release agent, and 1 part by weight of charge control agent "T-77" [manufactured by Hodogaya Chemical Co., Ltd.] were added, and the mixture was premixed using a Henschel mixer [FM10B manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], and then kneaded with a twin-screw kneader [IMC-9B20 manufactured by Imoto Machinery Co., Ltd.]. The resin particles were then finely pulverized using a supersonic jet mill, Labojet (manufactured by Nippon Pneumatic Mfg. Co., Ltd.), and classified using an air classifier (MDS-I, manufactured by Nippon Pneumatic Mfg. Co., Ltd.) to obtain resin particles with a volume average particle size of 5 μm and a particle size distribution of 1.2. The obtained resin particles (99 parts) were mixed with 1 part of a hydrophobic silica fluidizing agent, Aerosil R972 (manufactured by Nippon Aerosil), in a sample mill to obtain a toner.

[0098] <Low temperature fixability> (MFT) Toner is applied on the paper at 0.6mg / cm 2 The powder was evenly applied so that the density was 10 kg / cm. The powder was applied to the paper surface using a printer without a heat fixing unit. Other methods may be used as long as the powder can be evenly applied at the above weight density. The paper was then placed on the pressure roller at a fixing speed (heat roller peripheral speed) of 213 mm / sec and a fixing pressure (pressure roller pressure) of 10 kg / cm. 2 Under these conditions, the heating roller temperature was changed in the range of 90 to 230°C in 5°C increments to create fixed images at each temperature. Next, the presence or absence of cold offset in each fixed image was visually confirmed in ascending order of heating roller temperature, and the temperature at which cold offset no longer occurred is shown in Tables 1 and 2 as MFT (°C). The lower the temperature at which cold offset does not occur, the better the low-temperature fixing ability. Under these evaluation conditions, it is generally preferable that the MFT is 125° C. or less.

[0099] <Chargeability> (charge amount) 0.5g of toner and 10g of ferrite carrier (F-150, Powder Tech Co., Ltd.) were placed in a 50ml glass bottle, which was then conditioned for 8 hours at 23°C and 50% relative humidity. The glass bottle containing the conditioned toner was sealed and set in a Turbula shaker mixer and friction-stirred at 90 rpm for 2 minutes. 0.2g of the mixed powder after stirring was loaded into a blow-off powder charge measurement device equipped with a stainless steel mesh with a mesh size of 20μm. The charge of the remaining ferrite carrier was measured under conditions of a blow pressure of 10KPa and a suction pressure of 5KPa, and the charge of the toner (μC / g) was calculated by a standard method. For toner, the higher the negative charge amount, the better the charging characteristics are, and it is preferable that the negative charge amount is -15 μC / g or less. The charge amount was measured using a blow-off charge amount measuring device (manufactured by Toshiba Chemical Co., Ltd.).

[0100] <Heat-resistant storage stability> (degree of agglomeration) 1 g of toner and 0.013 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed in a shaker for 1 hour, the mixture was placed in a sealed container, and left to stand for 48 hours in an atmosphere at a temperature of 45°C and a humidity of 80%. The degree of cohesion was then measured using a powder tester, and the heat resistance storage stability was evaluated. The lower the value in the cohesion test determined by the following method, the more excellent the heat-resistant storage stability. Under these evaluation conditions, a value of 3% or less is preferable. Equipment: POWDER TESTER model PT-X (manufactured by Hosokawa Micron) Sieve openings: 355μm, 250μm, 150μm Vibration width: 1mm Vibration duration: 30 seconds Operation method: Set the sieves on the vibration table of the powder tester in the following order: top 355μm, middle 250μm, bottom 150μm. Place 1g of toner on the top sieve and vibrate with a vibration amplitude of 1mm for 30 seconds. Measure the weight of toner remaining on each sieve. Cohesion: Calculated from the weight of toner used for measurement and the weight of toner remaining after sieving. Cohesion degree (%)=(U / N+M / N×3 / 5+L / N×1 / 5)×100 U: weight of top row, M: weight of middle row, L: weight of bottom row, N: weight of sample (1g)

[0101] <Fixing strength> (Tape peeling) The fixing strength of the fixed image in the MFT prepared for the evaluation of low-temperature low-adhesion was evaluated by a tape peeling test. After attaching tape (3M's "Scotch Mending Tape") to the fixed image, the tape was peeled off and the image density (ID) of the image attached to the tape was measured with a reflection densitometer (product name "X-Rite model 404", X-Rite). The smaller the image density (number) of the attached image, the higher the fixing strength. Under these evaluation conditions, it is preferable that it is 0.2 or less.

[0102] <Fixing strength> (pencil hardness) The MFT-fixed image prepared in the above evaluation of low-temperature adhesion was subjected to a scratch hardness test in accordance with JIS K5600-5-4 (1999) by applying a load of 10 g from directly above a pencil fixed at a 45-degree angle by hand scratching, and the image strength was evaluated based on the pencil hardness at which the image was not scratched. The higher the pencil hardness, the better the image strength. Generally, it is preferable that the pencil hardness is HB or higher.

[0103] As is clear from the evaluation results in Tables 1 and 2, the toner binders (D-1) to (D-10) containing the crystalline polyester resins (A-1) to (A-10) of Examples 1 to 10 were evaluated to be excellent in heat-resistant storage stability, electrostatic charge property, and dispersibility of the crystalline polyester in the amorphous resin. On the other hand, the toner binders (DR-1) to (DR-6) containing the crystalline polyester resins (AR-1) to (AR-6) of Comparative Examples 1 to 6 were poor in at least one of the performance items of heat-resistant storage stability, electrostatic charge property, and dispersibility. [Industrial Applicability]

[0104] The crystalline polyester resin of the present invention can be suitably used as a toner for electrophotography used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. Further, it is suitable for use as an additive for paints, an additive for adhesives, particles for electronic paper, and the like.

Claims

1. A toner binder comprising a crystalline polyester resin (A) which is a polycondensate of a polyol component (x), a polycarboxylic acid component (y), and a modified silicone compound (z), wherein the polyol component (x) contains 80 mol % or more of a linear aliphatic diol (x1) having an even carbon number and 2 to 24 carbon atoms, based on the number of moles of the polyol component (x), and the polycarboxylic acid component (y) contains 80 mol % or more of a linear aliphatic dicarboxylic acid (y1) having an odd carbon number and 3 to 23 carbon atoms, based on the number of moles of the polycarboxylic acid component (y), and the silicon element content (X1) measured by fluorescent X-ray analysis is 1.0 to 1.0 mol %. S ) is from 1.0 to 5.0 weight percent based on the weight of the toner binder.

2. 2. The toner binder according to claim 1, wherein the content of the cyclic ester compound which is a reaction product of the polyol component (x) and the polycarboxylic acid component (y) is 0.7 to 7.0% by weight based on the weight of the toner binder.

3. 3. The toner binder according to claim 1, wherein the modified silicone compound (z) is a modified silicone having at least one functional group selected from a hydroxyl group, an amino group, and a carboxy group.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP2002287426A

  • Toner for electrostatic charge image development

    JP2023018981A